Fish Fauna Diversity in Relation to Environmental Parameters in Muthukuda Mangroves Southeast Coast of Tamil Nadu, India - Vasanthi, Natarajan; Muthukumaravel, Kannayiram (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The seasonal variations of physico-chemical parameters on fish faunal diversity were studied in Muthukuda mangrove (Latitude 9o36’N and Longitude 78o83’E) waters from July 2022 to June 2023. The atmospheric temperature and water temperature ranged from 27.7 to 34.9°C and 25.8°C to 30.9°C respectively. The Hydrogen ion concentration of water varied from 7.3 to 8.3. The dissolved oxygen was ranged from 7.3 to 8.3. Salinity fluctuated between 10.5 to 31.9‰. The nutrients such as total phosphorus, nitrate and silicate ranged from 0.7 to 3.2 µg/l, 5.1 to 13.7 µg/l and 9.2 to 71.2 µg/l respectively. The dissolved oxygen and nutrients were found to be low in summer and high during the monsoon season. Similarly, temperature, pH and salinity were low during the monsoon season and high during the summer season. Fish faunal diversity from Muthukuda mangroves comprises 19 species representing 5 orders, 17 families and 19 genera. The order Perciformes were dominated by 13 species followed by Clupeiformes and Siluriformes 02, Gonorphynchiformes and Beloniformes with one species each. The higher diversity values in fish fauna observed in the present investigations clearly elucidated the healthy nature of Muthukuda mangroves.